Evaluation of 3, 4, 4, 9-trichlorocarbanilide to zebrafish developmental toxicity based on transcriptomics analysis. (September 2021) - He, Liting; Chen, Yuanyao; Hu, Zhiyong; Zhang, Yuan; Wang, Yongfeng; Wei, Jiajing; Fan, Zunpan; Xu, Jia; Peng, Meilin; Zhao, Kai; Zhang, Huiping; Liu, Chunyan
Abstract: Triclocarban (TCC), considered an endocrine-disrupting, persistent, and bioaccumulating organic matter, has attracted a great deal of attention for its pollution and health risks. However, studies on its toxicological mechanism, especially for embryo development are limited. This article explores the cardiac developmental toxicity induced in zebrafish embryos after exposure to different TCC concentrations. First, liquid chromatography-tandem mass spectrometry was used in detecting TCC in embryos in vivo after exposure to various TCC. Results showed that embryonic TCC content reached 9.23 ng after exposure to 300 μg/L TCC, the heart rates of the embryos markedly decreased, heart abnormalities significantly increased. In addition, obvious pericardial effusion was observed in the larvae. Through transcriptome sequencing, 200 differential gene expression (DGE) patterns were detected in the TCC (300 μg/L) experimental and control groups. The results of GO function analysis and KEGG pathway of DGE showed that aryl hydrocarbon receptor (AhR) activation and cyp-related genes ( cyp1a, cyp1b1 and cyp1c ) were significantly up-regulated. these affected the normal development of zebrafish embryonic heart, tissue edema, and hemorrhage. TCC exhibited strong cardiac teratogenic effects and developmental toxicity, which is partly related to AhR activation. Transcriptome-based results are helpful in precisely determining the risk of TCC exposure. The potential mechanism between TCC and AhR should be further investigated. Graphical abstract: Image 1 Highlights: Embryonic TCC content reached 9.23 ng after exposure to 300μg/LTCC. TCC exhibited strong cardiac teratogenic effects. RNA-seq indicates that cardiac abnormalities in zebrafish is partly related to AhR activation.